2017
DOI: 10.1016/j.cell.2017.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A-Retinoic Acid Signaling Regulates Hematopoietic Stem Cell Dormancy

Abstract: Dormant hematopoietic stem cells (dHSCs) are atop the hematopoietic hierarchy. The molecular identity of dHSCs and the mechanisms regulating their maintenance or exit from dormancy remain uncertain. Here, we use single-cell RNA sequencing (RNA-seq) analysis to show that the transition from dormancy toward cell-cycle entry is a continuous developmental path associated with upregulation of biosynthetic processes rather than a stepwise progression. In addition, low Myc levels and high expression of a retinoic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
283
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 368 publications
(312 citation statements)
references
References 82 publications
(124 reference statements)
28
283
1
Order By: Relevance
“…When RA is limited via dietary uptake, HSC are activated to proliferate and differentiate. 79 This is in line with findings that loss of the RA receptor retinoic acid receptor c (RARc) leads to decreased HSC number and increased differentiation. 80 The same study also showed that RARc activation increases the self-renewing capacity of HSC.…”
Section: Amino Acids a Keystone For Bm And Immune Cell Differentiatisupporting
confidence: 83%
“…When RA is limited via dietary uptake, HSC are activated to proliferate and differentiate. 79 This is in line with findings that loss of the RA receptor retinoic acid receptor c (RARc) leads to decreased HSC number and increased differentiation. 80 The same study also showed that RARc activation increases the self-renewing capacity of HSC.…”
Section: Amino Acids a Keystone For Bm And Immune Cell Differentiatisupporting
confidence: 83%
“…Deletion of this element globally reduced HoxB expression in HSCs, resulting in changes to downstream signaling pathways, and loss of HSC selfrenewal and reconstitution capacity (Qian et al, 2018). These findings demonstrate pivotal roles for RA signaling in the stem cell niche (Cabezas-Wallscheid et al, 2017;Chanda, Ditadi, Iscove, & Keller, 2013;Ghiaur et al, 2013;Qian et al, 2018) Table 1). There are several RAREs found within and immediately flanking the Hox complexes (Figures 2 and 4).…”
Section: Ra Signaling and Hox Gene Regulation In The Hematopoietic mentioning
confidence: 86%
“…To this end, several groups have confirmed the pro-differentiation role of retinoids on human HSCs [47, 48] while elegant studies in murine models have shown the opposite effects [49, 50]. While in-depth studies to explain these interspecies differences are lacking, analysis of published data hint towards potential explanations for observed differences.…”
Section: Regulation Of Stemness By the Microenvironment’s Control Of Ramentioning
confidence: 99%